Penerapan Asesmen Formatif Berbasis LKPD Untuk Meningkatakan Pemahaman Siswa - Andesta Prayoga; Mifta Hul Khairi; Sintia Dwipa Anjani; Yenda Julpita Sari; Zanuba Nur Rahma (Yayasan Darussalam Bengkulu, 2024)
This study aims to describe the implementation of worksheet-based formative assessment and analyze its impact on the understanding of second-grade students at SDN 99 Bengkulu City. The study involved 23 students using a qualitative descriptive method through observation, analysis of worksheet results, and formative assignments. Worksheets help students review and revise their answers with the support of teacher feedback. The results showed an increase in student understanding, reflected in the ability to complete assignments, correct errors, and explain the material better. Students also became more independent and interested in learning because the worksheets were designed according to their development. Teachers considered the worksheets very helpful in the learning process. Thus, worksheet-based formative assessment is effective in improving understanding and meaningful learning in lower grades.